2015
DOI: 10.1103/physrevb.91.104411
|View full text |Cite
|
Sign up to set email alerts
|

Transitions to valence-bond solid order in a honeycomb lattice antiferromagnet

Abstract: We use Quantum Monte-Carlo methods to study the ground state phase diagram of a S = 1/2 honeycomb lattice magnet in which a nearest-neighbor antiferromagnetic exchange J (favoring Néel order) competes with two different multi-spin interaction terms: a six-spin interaction Q3 that favors columnar valence-bond solid (VBS) order, and a four-spin interaction Q2 that favors staggered VBS order. For Q3 ∼ Q2 J, we establish that the competition between the two different VBS orders stabilizes Néel order in a large swa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 72 publications
(176 reference statements)
4
62
0
Order By: Relevance
“…The positive value of y 3 indicates that the Néel-VBS transition on the honeycomb lattice should not be in this universality class, and would most likely be driven first order. Quantum MC results for such systems [20,32,33] have seen no clear evidence of a first-order transition, although a trend in this direction with increasing system size has been suggested [20]. Our results indicate that the true nature of this transition is indeed first order, but the small value of y 3 is consistent with critical behavior, described by the NCCP 1 universality class, over a range of length scales.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…The positive value of y 3 indicates that the Néel-VBS transition on the honeycomb lattice should not be in this universality class, and would most likely be driven first order. Quantum MC results for such systems [20,32,33] have seen no clear evidence of a first-order transition, although a trend in this direction with increasing system size has been suggested [20]. Our results indicate that the true nature of this transition is indeed first order, but the small value of y 3 is consistent with critical behavior, described by the NCCP 1 universality class, over a range of length scales.…”
Section: Discussionsupporting
confidence: 46%
“…Even allowing for the large and unconventional finite-size effects in this system [7,13], it seems unlikely that y 3 would be more than very weakly irrelevant, which would mean that three-fold anisotropy should be visible over moderate length scales in the JQ model on the honeycomb lattice. Pujari et al [33] have recently reported evidence of such anisotropy at the critical point.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other models were therefore pursued. In the J-Q model [15], the Heisenberg exchange J between S = 1/2 spins is supplemented by a VBS-inducing four-spin term Q which is amenable to efficient quan-tum Monte Carlo (QMC) simulations [15,16,17,18,19,20,21,22,23]. Although many results for the J-Q model support the DQC scenario, it has not been possible to draw definite conclusions because of violations of expected scaling relations that affect many properties.…”
mentioning
confidence: 99%
“…Other models were therefore pursued. In the J-Q model [15], the Heisenberg exchange J between S = 1/2 spins is supplemented by a VBS-inducing four-spin term Q which is amenable to efficient quan-1 tum Monte Carlo (QMC) simulations [15,16,17,18,19,20,21,22,23] Here we show that the DQC puzzle can be resolved based on a finite-size scaling Ansatz including the two divergent length scales of the theory-the standard correlation length ξ, which captures the growth of both order parameters (ξ Néel ∝ ξ VBS ), and a faster-diverging length ξ associated with the thickness of VBS domain walls and spinon confinement (the size of a spinon bound state). We show that, contrary to past assumptions, ξ can govern the finite-size scaling even of magnetic properties that are sensitive only to ξ in the thermodynamic limit.…”
mentioning
confidence: 99%